OPTIMALISASI PEMANFAATAN AMPAS KELAPA MELALUI IMPLEMENTASI MESIN PENEPUNG DI DESA JERUJU BESAR - Fitri Imansyah; Ivan Sujana; M. Iqbal Arsyad (Universitas Mataram, 2023)
Jeruju Besar Village, which is located in Sungai Kakap District, Kubu Raya Regency, West Kalimantan, has several plantation and agricultural products that are potentially feasible for further development. One of the interesting plantation products is coconut. After conducting a survey, it was found that residents of Jeruju Besar Village only sell whole coconuts or only process them into coconut milk, while the coconut pulp that has been squeezed is simply thrown away. The discarded coconut dregs are buried next to residents' houses, causing an unpleasant odor for quite a long time. Based on these conditions, the team then had the idea to make a coconut pulp flour machine to develop village community UMKM so that villages could market coconut products more broadly. Through the community service program, this activity also aims to change the traditional view of coconut dregs into a valuable resource through processing using a Smoothing Flour machine. This processing produces value-added products, such as powders and organic fertilizers. Through collaboration with the government, community organizations and activity partners, the people of Jeruju Besar Village are empowered with new knowledge and skills in processing coconut pulp and operating flour machines. The resulting positive impacts include increasing people's income, increasing welfare, reducing organic waste, and changing people's views of coconut dregs. This activity also provides sustainable economic, environmental and social benefits and produces sustainable positive changes in environmental, economic, social and educational aspects in Jeruju Besar Village great and the surroundings.